2018
DOI: 10.1111/imb.12555
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns and colocalization of two sensory neurone membrane proteins in Ectropis obliqua Prout, a geometrid moth pest that uses Type‐II sex pheromones

Abstract: Sensory neurone membrane proteins (SNMPs) function as essential cofactors for insect sex pheromone detection. In this study, we report two SNMPs in Ectropis obliqua Prout, a serious geometrid pest that produces typical Type‐II sex pheromones. Sequence alignments and phylogenetic analyses showed that EoblSNMP1 and EoblSNMP2 belong to two distinct SNMP subfamilies. Quantitative real‐time PCR suggested that EoblSNMP1 was male antennae‐biased, whereas EoblSNMP2 was highly expressed on male antennae but was also ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…SNMP was first identified from Lepidoptera and exhibited high expression in pheromone receptor neurons of the antennae (Rogers et al, 2001). Since then SNMP2 has been found that is expressed in antennae but also other tissues and is thought to be involved in multiple olfactory roles (Sun et al, 2018). The SNMP2 gene was also found in the transcriptome of H. zea PG and tarsi.…”
Section: Discussionmentioning
confidence: 99%
“…SNMP was first identified from Lepidoptera and exhibited high expression in pheromone receptor neurons of the antennae (Rogers et al, 2001). Since then SNMP2 has been found that is expressed in antennae but also other tissues and is thought to be involved in multiple olfactory roles (Sun et al, 2018). The SNMP2 gene was also found in the transcriptome of H. zea PG and tarsi.…”
Section: Discussionmentioning
confidence: 99%
“…SNMPs are divided into SNMP1 and SNMP2 subgroups (Forstner et al, 2008). Notably, SNMPs are known to participate in pheromone detection (Jin, Ha & Smith, 2008;Pregitzer et al, 2014;Sun et al, 2019), although the molecular mechanisms of their involvement in chemoreception are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Two SNMPs have distinct 1. expression patterns in the antennal sensilla of Ectropis obliqua (Sun et al, 2019b), suggesting a functional diversification between the two genes. In D. melanogaster, H. virescens, and B. mori, SNMP1s play critical roles in pheromone signaling (Jin et al, 2008;Pregitzer et al, 2014;Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on Heliothis virescens and Antheraea polyphemus demonstrated that SNMP1 s are co-expressed with PR s in the pheromone-responsive neurons, whereas SNMP2 s are expressed in the supporting cells around the neurons ( Forstner et al, 2008 ). Two SNMP s have distinct expression patterns in the antennal sensilla of Ectropis obliqua ( Sun et al, 2019b ), suggesting a functional diversification between the two genes. In D. melanogaster , H. virescens , and B. mori , SNMP1s play critical roles in pheromone signaling ( Jin et al, 2008 ; Pregitzer et al, 2014 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation